Pengaruh Service Quality dan After Sales Service terhadap Customer Loyalty pada OPS Garage - Ardiansyah, Muhammad Farhan; Isyanto, Puji; Sumarni, Neni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to ascertain and elucidate the relationship between after-sale support and service quality and customer happiness at OPS Garage. Multiple linear regression was used for data analysis and questionnaires were used for data collecting in this quantitative study. According to the study's findings, OPS Garage customers are positively and significantly impacted by both loyal customers and high-quality services. Customer happiness is positively and significantly impacted by service quality. The two factors under investigation customer loyalty and service quality have a favorable and substantial impact on satisfaction levels at the same time. Keywords: After sales service, Service Quality, Consumer Loyalty.